Mosquito (Diptera: Culicidae) grouping based on larval habitat characteristics in high mountain ecosystems of Antioquia, Colombia (2018)
ABSTRACT : Information about mosquito ecology in the high mountain ecosystems of the Neotropical region is sparse. In general, few genera and species have been reported in these ecosystems and there is no information available on habitats and the mosquitoes occupying them. In the present study, specimens collected from NW Colombia in HME were grouped using larval habitat data via an Operational Taxonomic Unit (OTU) determination. A total of 719 mosquitoes was analyzed belonging to 44 OTUs. The analysis considered habitat features and clustered the specimens into six groups from A-F. Five of these included species from different genera, suggesting common habitat requirements. Group E with four genera, seven subgenera, and six species occupied the highest areas (above 3,000 m), whereas three groups (B, D, F) were detected at lower altitudes (1,960-2,002 m). Bromeliads were the most common larval habitat, with 47% (335/719) of the specimens; five genera, six subgenera, and eight species were identified and classified into 66% (29/44) of the OTUs. This work showed some similarities to the habitat requirements and provides a grouping system that constitutes an important baseline for the classification of mosquito fauna from high mountain ecosystems according to altitude and larval habitat.